Load Carrying Capacity of Corrugated Web Beam - Naji, Raged Nassry; Chkheiwer, Aqeel H. (Basrah Journal for Engineering Sciences, 2023)
The shear panels of plate girder made from corrugated in the web is investigated in this research. A corrugated web beam of plate is attached in the shear zone of the web as part of an experimental and theoretical investigation into plate girders. In experiments, seven plate girder specimens were tested under two points of load. Six of them were made of different shape of corrugated plate in the web, the last specimen was tested without corrugation as a reference specimen called control. In this study investigated the effected of (corrugation plate, thickness of corrugation with number layers of corrugated and the shape of corrugated plate) on (buckling and ultimate loads also on lateral and vertical deflection) and compared with reference specimen, these specimens have the same dimensions, the main variable was the thickness of the corrugated plate in the web (0.5, 1, and 2) mm, the depth was constant (300 mm). According to results of the experiment, the corrugated plates primarily increase the plate girder's stability. A corrugation of plate increases the buckling load and ultimate load significantly through the contribution of the corrugation to delay buckling of the plate girder in the web. In addition, it was found that increasing the plate-girder thickness leads to increased buckling and ultimate loads, because the stiffness will increase and delay the buckling. Also, the trapezoidal corrugation and the diagonal corrugate that placed perpendicular on the tension field action, give higher buckling and ultimate load than control beam. Ansys (version 17.0) computer program was used in this research represent the steel and nonlinear large structural shell was used to represent the corrugated web beam of the plate in the finite element analysis model.